Effects of Vacation Rental Websites on the Concentration of Tourists-Potential Environmental Impacts. An Application to the Balearic Islands in Spain - Martín Martín, José María; Rodríguez Martín, José Antonio; Zermeno Mejia, Karla Aida; Salinas Fernández, José Antonio (International Journal of Environmental Research and Public Health, 2018)
The concentration of tourists at certain times of the year can damage sensitive environments. The use of peer-to-peer vacation rental websites has increased greatly during the last decade. This system could either reduce seasonality in touristic destinations where the tourist activity takes place throughout the year at a lower price or on the contrary, it could increase the number of visitors at certain times of the year even more. This paper intends to analyze the effect that these platforms have on tourism seasonality in order to calculate if they help reduce or increase the pressure on the destinations. To do so, the Gini Index has been applied to one of the main touristic spots in Europe, the Balearic Islands in Spain. The conclusion is that this type of accommodation has aggravated the problem, generating a greater concentration of tourists and a higher pressure on the resources of the islands.
Keywords: Spain; environmental impacts; environmental impacts; collaborative economy; peer-to-peer vacation rental websites; seasonality of tourism; JCR; Scopus